Research staff’s experiences of how the COVID-19 pandemic impacted recruitment for a paediatric network study - Isobel Fishman; Suzanne Henderson; Christina Vadeboncoeur (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Since the COVID-19 pandemic, a paediatric network study with clinical sites across Canada suffered a reduction in participation. When research studies fail to meet enrolment targets, it can reduce the strength and validity of the results. This study explores research staff’s experiences of how the COVID-19 pandemic impacted recruitment for a paediatric network study. Methods This study was conducted using a qualitative design. Focus group sessions were used to gain the perspective of research staff involved in recruitment and transcripts were analysed using Colaizzi’s seven-step method of data analysis. Results Analysis revealed four major themes: (1) the COVID-19 pandemic had an impact on research activity; (2) families of children with medical complexity perform a risk-benefit assessment when deciding whether to take part in research; (3) a trusting relationship with clinicians is a key factor in research recruitment; and (4) research needs to be flexible in order to adapt to evolving contexts. Conclusion This study identified both COVID-19 and non-COVID-19-related factors that impacted study recruitment for a paediatric network study. Understanding and addressing these challenges will mitigate the negative impacts on health outcomes that can occur when research studies fail to meet enrolment targets.